Pattern of stress and anxiety behaviour among people with type 2 diabetes in a tertiary care hospital of Delhi, India: an observational study - Ranjan, Prakash; Das, Jayanta K. (International Journal of Advances in Medicine, 2020)
Background: The prevalence of stress and anxiety in diabetes is considerably higher than normal population and found to have a negative impact on diabetes. The aim of this study was to examine the relationships among perceived diabetes-related stress and anxiety behaviors in adults living with type 2 diabetes (T2DM). Methods: In this descriptive and cross sectional study, systematic random sampling technique was used to select the sample of type 2 diabetic patients. Scheduled interview of 412 type 2 diabetic patient was conducted at outpatient department of a tertiary care hospital in New Delhi. Results: Out of 412 diabetic patients, 58.7 percent feel diabetes-related stress and anxiety behaviors when they think about living with diabetes. Age of patients, educational status, occupation and average monthly family income of diabetic patients are statistically associated with perceived diabetes-related stress and anxiety behaviors of type 2 diabetes mellitus patients. Lifestyle behaviour like diet pattern (vegetarian or nonvegetarian diet) and moderate intensity activities like walking are also statistically associated with perceived diabetes-related stress and anxiety behaviors of type 2 diabetes mellitus patients. Conclusions: This study found a high prevalence of diabetes-related stress and anxiety behavior in patients with Type 2 DM. Therefore, the care of individuals with type 2 Diabetes Mellitus (DM) should include the screening and possible management of stress and anxiety in order to achieve and sustain treatment goals.